ANALISIS PERBANDINGAN NOVEL “MUTIARA DI KOTA MELBOURNE ” DAN “FOUR SEASONS IN BELGIUM” DENGAN PENDEKATAN MIMETIK - Seles, Susi (DISASTRA: PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2019)
Comparative literature is interesting to observe. The use of a mimetic approach may indicate an art of presentation or imitation, implying something static; mimetic involves something dynamic, a process, an active relationship with the reality of life. The purpose of this study to find out how the comparison of the novel "Pearl in the city of melbourne" and "Four seasons in belgium" through the mimetic approach. This research was conducted using descriptive research,  that presented the results found in the comparison of two novels with mimetic approach. From these analyzes using the mimetic approach found that there are similarities between the two works of literary novel is the similarity of the title that takes place setting abroad and describes stories that pamper the mind with the beauty of abroad. In addition these two novels illustrate how the life stories of people who fight for love but do not reciprocate because his lover more priority to career than love